Financial regulations - Federal Republic of Nigeria (Lagos : Federal Government Press, 2000)
This book contains the rules and regulations guiding Public Service in the Fedreal Republic of Nigeria.
Cover title.
gp. 25/03/2019
Loans
Keywords: Economic; Budget